Understanding gender bias in teachers' grading: The role of gender stereotypical beliefs. (October 2022) - Doornkamp, L.; Van der Pol, L.D.; Groeneveld, S.; Mesman, J.; Endendijk, J.J.; Groeneveld, M.G.
Abstract: This study experimentally tested the influence of secondary school students' gender on Dutch language and math teachers' grading ( n  = 358) and examined the role of teachers' gender and gender stereotypes in gender grading bias. Results showed that grading, on average, was not gender biased. However, differences between teachers' gender grading bias were related to their gender stereotypes. Although we found no direct effect of teachers' gender on grading bias, for math we found an indirect effect through their gender stereotypes. This study provides evidence for the role of teachers' gender stereotypes in gender grading bias that thus far had only been assumed.